Possible Contribution of Mineralocorticoid Receptor Activation on Glucocorticoid-Induced Left Ventricular Remodeling in Adrenalectomized Rat - Islam, Kazi Rafiqul; Sherjee, Shamshad J; Mori, Hirohito; Kobara, Hideki; Nishiyama, Noriko; Moitry, Nazia F; Nakano, Daisuke; Mostofa, Mahbub; Nishiyama, Akira (Journal of Bangladesh Society of Physiologist, 2013)
Background: Chronic glucocorticoid treatment induces the development of renal injury via mineralocorticoid receptor (MR) activation in bilaterally adrenalectomized rats. It has been hypothesized that glucocorticoid contributes to the development of left ventricular (LV) remodeling through MR activation in bilaterally adrenalectomized rats (ADX). Methods: ADX rats were maintained with 1%NaCl in drinking water and randomly treated as follows for 8 weeks: vehicle (n=7), bilateral adrenalectomy (ADX) + hydrocortisone (HYDRO) (5 mg/kg/day, subcutaneous, n=7), and ADX + HYDRO + eplerenone (0.125% in chow; approximately 75 mg/kg/day, n=7). An osmotic minipump was implanted subcutaneously for continuous infusion of HYDRO. Results: As compared with control vehicletreated uninephrectomized rats, ADX+HYDRO treatment for 8 weeks significantly increased systolic blood pressure, LV weight, collagen content and mRNA levels of atrial natriuretic peptide, brain natriuretic peptide, and collagen type 1 and III. These changes were associated with increase in LV thiobarbituric acid reactive substances content, dihydroethidium fluorescence and mRNA levels of NADPH oxidase subunits. Treatment with a selective MR antagonist, eplerenone significantly attenuated HYDRO induced changes in LV parameters. HYDRO-induced increases in mRNA and protein levels of serum and glucocorticoid-regulated kinases 1 were prevented by eplerenone. Conclusion: These data suggest that chronic glucocorticoid treatment induces LV tissue remodeling through MR dependent mechanism in bilateral adrenalectomized rats. DOI: http://dx.doi.org/10.3329/jbsp.v8i1.16639 J Bangladesh Soc Physiol. 2013, June; 8(1): 6-15